2003
DOI: 10.1111/1467-8624.00604
|View full text |Cite
|
Sign up to set email alerts
|

Studying the Effects of Early Child Care Experiences on the Development of Children of Color in the United States: Toward a More Inclusive Research Agenda

Abstract: Evidence is presented of the different cultural and ecological contexts affecting early child care for families of color. It is argued that improvements on previous research require a fundamental shift in how race, ethnicity, and culture as psychological variables are examined. Furthermore, to avoid the pitfalls and failures of previous research, new research must incorporate expanded models of child care and development in childhood. The integrative model of development for children of color proposed by Garci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
52
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(56 citation statements)
references
References 96 publications
(100 reference statements)
3
52
1
Order By: Relevance
“…In terms of implications for developmental theory, the findings underscore the value of heeding Garcia Coll, Ackerman, and Cicchetti's (2000) exhortation that for all little-explored populations, applied developmental scientists must ascertain, through rigorous within-group studies, the relative salience of overlapping indexes processes within that particular context (see also Johnson, Jaeger, Randolph, Cauce, & Ward, 2003). Results showed that counter to widespread beliefs about the destructive overscheduling of wealthy youth, activity involvement generally had mild positive associations if anything; it was aspects of family dynamics that were of much more significance.…”
Section: Limitations Implications and Future Directionsmentioning
confidence: 99%
“…In terms of implications for developmental theory, the findings underscore the value of heeding Garcia Coll, Ackerman, and Cicchetti's (2000) exhortation that for all little-explored populations, applied developmental scientists must ascertain, through rigorous within-group studies, the relative salience of overlapping indexes processes within that particular context (see also Johnson, Jaeger, Randolph, Cauce, & Ward, 2003). Results showed that counter to widespread beliefs about the destructive overscheduling of wealthy youth, activity involvement generally had mild positive associations if anything; it was aspects of family dynamics that were of much more significance.…”
Section: Limitations Implications and Future Directionsmentioning
confidence: 99%
“…In response to such findings, Johnson et al (2003) proposed several criticisms of the research that has been conducted on children of color in child care environments. One concern is the extent to which current measures of quality are able to measure constructs such as racial socialization.…”
Section: Classroom Quality and Ethnicity Of Teachers And Childrenmentioning
confidence: 99%
“…With a need to create "more specific and culturally relevant definitions of quality" (Johnson et al, 2003(Johnson et al, , p. 1239 in child care, current measures of child care quality should be examined in a variety of contexts. However, if teachers utilize methods that are considered to be culturally appropriate but do not meet the dominant culture's ideas of quality, then pressure to conform to Euro-centric standards of quality challenges culturally relevant pedagogy in early childhood classrooms.…”
Section: Classroom Quality and Ethnicity Of Teachers And Childrenmentioning
confidence: 99%
“…In Southeast Florida, particularly in Miami-Dade County, the Latino population has grown exponentially within the last several decades (U.S. Census Bureau, 2008), a reason why research needs to be more inclusive (Johnson et al, 2003 (Garcia & Jensen, 2009). …”
Section: Latinos In Early Childhood Researchmentioning
confidence: 99%
“…According to Johnson et al (2003), development in Latino children cannot be based on universal notions, instead it should be based on their specific ecological surroundings. For example, literature has suggested that positive school environments will mostly benefit the underprivileged Latin American populations, especially those children coming from Mexico (Han, 2008), which parallels the population of children residing in Southeast Florida.…”
Section: Latinos In Early Childhood Researchmentioning
confidence: 99%